Cultural and emotional identification with Madrid through TV series of Valeria (Netflix: 2020-2023) - Higueras Ruiz, María José (2023)
VoD -video on demand- platforms have promoted a global television market in the current audiovisual industry. Thanks to its transnational character, the operator of Netflix distributes around the world TV series produced inside a local context, and national cultural identities are transmitted in a global context. The present paper aims to determine the Spanish idiosyncrasy through images about the city of Madrid in Netflix original fiction: Valeria (2020-2023). A qualitative methodology has been used to conduct a bibliographic review and examine this TV fiction. To do so, we elaborate an analysis table with technical data, cultural and emotional identification, and audiovisual language in scenes which show places of Madrid. Findings show the inclusion of outdoors and architectures, locals of economic activity, and identity symbols across images which articulate personal and professional stories with a suitable audiovisual filmmaking. Conclusions highlight the cultural proximity for a local audience, and touristic options of Madrid through this TV series and its promotional material.